TATA KELOLA PEMERINTAHAN DAERAH DALAM PEMBANGUNAN JALAN DI KECAMATAN KAMPAR KIRI TAHUN 2021-2022 - Firmansyah, Febri; ,, Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Infrastructure development, particularly roads, is a key indicator of improving public welfare and driving regional economic growth. This study aims to analyze the governance of the Kampar Regency government in road infrastructure development in Kampar Kiri District. The main focus of this study is to evaluate the extent to which the principles of good governance, such as Fairness, Transparency, Accountability, Responsiveness, and Participation, are implemented in the development process. The approach used in this study is qualitative. Data collection techniques include in-depth interviews with relevant parties, direct field observations, and documentation studies of road development policies and programs. Data analysis is conducted descriptively to understand the governance practices implemented and the obstacles faced by the local government in road development. The research results show that the local government has made efforts to implement good governance principles in road construction in Kampar Kiri District. However, the implementation of these principles still faces various obstacles, including weak coordination between stakeholders, budget constraints, and minimal community participation in development planning and oversight. These conditions hamper the effectiveness of sustainable and equitable road development. Therefore, a more inclusive and collaborative governance strategy is needed between the government, the community, and the private sector to improve the quality and sustainability of infrastructure development. Keywords: Governance, Road Development, Good Governance.